(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
As a close-fitting clothing for women, bras are in direct contact with women’s breasts and fully fit. The bra structure design based on the difference between upper and lower busts cannot meet individual differences. To solve the problem that traditional large-scale bra production methods cannot meet the individual needs of consumers For this problem, a parametric design method for one-person-one-version personalized bra samples is proposed. By analyzing the morphological characteristics of different breast shapes and the composition factors of bra samples, the breast is regarded as a combined model of ellipsoid and cone. The geometric model of breast shape is established, and the model is analyzed by surface flattening technology, and then the breast is obtained. Mathematical representation of breast characteristic structure lines include root circumference, surface arc length, and lower teat cup arc. According to the relationship between the breast and the size of the bra sample, the parametric relationship model of the bra sample is obtained, and the knowledge model of the bra sample is constructed based on the relationship model, which provides a method for realizing the personalization of the bra sample.